2014
DOI: 10.4021/jmc1630w
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Chylothorax. An Unusual Presentation in the Course of Immune Reconstitution Inflammatory Syndrome, HIV Infection and Kaposi’s Sarcoma: A Case Report

Abstract: Immune reconstitution inflammatory syndrome (IRIS) is a term used to describe the paradoxical worsening of a pre-existing infection or the presentation of a previously undiagnosed condition in HIV-infected patients soon after commencement of antiretroviral therapy (ART). We report a case of a patient with HIV infection and Kaposi sarcoma, who developed bilateral chylothorax as a manifestation of IRIS, after the initiation of highly active antiretroviral therapy. Bilateral chylothorax is extremely rare and has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Our search of previous literature on PubMed revealed only 18 cases, among which 17 were HIV-positive patients and one was an HIV-negative patient; 13 had chylothorax, 2 had chylous ascites, and 3 had both. After treatment, 6 patients survived while 12 died, resulting in a mortality rate of approximately 66.7% (Table 1) [4][5][6][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. * The two patients labeled as 'likely HIV positive' came from case reports published in 1986 and 1988, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search of previous literature on PubMed revealed only 18 cases, among which 17 were HIV-positive patients and one was an HIV-negative patient; 13 had chylothorax, 2 had chylous ascites, and 3 had both. After treatment, 6 patients survived while 12 died, resulting in a mortality rate of approximately 66.7% (Table 1) [4][5][6][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. * The two patients labeled as 'likely HIV positive' came from case reports published in 1986 and 1988, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Cherian et al depicted a case of chylothorax in an HIV-associated KS patient that showed improvement after four months of systemic chemotherapy, a medium chain triglyceride (MCT) diet, percutaneous chest tube drainage, and talc pleurodesis treatment [10]. A review of the literature reveals that, apart from symptomatic supportive therapy, all patients with Kaposi's sarcoma who developed chylous effusions and had a favorable prognosis received timely systemic chemotherapy [10,12,14,[20][21][22]. In our case, the patient also achieved a positive outcome after being treated with chemotherapy in addition to antiretroviral therapy and local symptomatic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…KS-related chylothorax is described by a few authors as an unusual manifestation of KS,16–19 one of which also in context of IRIS 18. This could be explained due to metastatic KS in the thoracic duct and adjacent mediastinal structures, to in situ KS in the thoracic region20 or, probably, due to the negative intrathoracic pressure of the thorax, which drew ascitic fluid into the pleural space.…”
Section: Discussionmentioning
confidence: 99%